Legal privilege and transnational evidence-taking : a comparative study on cross-border disclosure, evidence-shopping and legal privilege / René Jansen. - Jansen, René, 1990- (Intersentia, 2023)
Certain confidential lawyer-client communications are privileged from disclosure. Considering that these rules can differ from state to state, this book examines various states' disclosure laws and legal privilege rules in a comparative manner. It proposes a new rule that courts should use for determining the applicable privilege law during transnational litigation.